A review of botany, phytochemistry, and pharmacology of the forest Natal mahogany (Trichilia dregeana Sond.) - Alfred Maroyi (Journal of Applied Pharmaceutical Science, 2024)
Trichilia dregeana is an underutilized plant species native to tropical Africa and known for its nutritional and medicinal properties. The present review compiles existing information on botany, traditional uses, and chemical and pharmacological properties of T. dregeana. Multiple searches on existing literature on the traditional, medicinal, phytochemistry, and pharmacological properties of T. dregeana were conducted in online databases such as Scopus®, Google Scholar, SpringerLink®, SciELO, ScienceDirect®, PubMed® and Web of Science, as well as using pre-electronic literature sources obtained from the university library. Trichilia dregeana is used as a medicinal plant against human and animal diseases in seven countries, that is, 33.3% of the countries where the species is indigenous. The phytochemical evaluation of the plant revealed that it contains alcohols, alkanes, amides, esters, lignan, limonoids, sesquiterpenes, steroids, and triterpenoids. The pharmacological assessments showed that the crude extracts and phytochemical compounds isolated from the species demonstrated antibacterial, antifungal, antimycobacterial, antiviral, acetylcholinesterase, anti-inflammatory, antioxidant, insecticidal, prostaglandin-synthesis inhibitory, nitric oxide production inhibitory, wound healing, mutagenicity, and toxicity activities. Detailed studies focusing on toxicity and safety, mechanisms of action in vivo, and clinical research aimed at corroborating the traditional medical applications of T. dregeana are recommended.
Keywords: Indigenous pharmacopeia, mahogany, Meliaceae, traditional medicine, Trichilia dregeana, tropical Africa